Hubungan Karakteristik Individu dengan Jaringan Komunikasi pada Kelompok Wanita Tani (Suatu Kasus di KWT KSB Desa Sukaraja Kabupaten Bogor) - Jonri, Noerwita Alieffia; Fatimah, Sri (Universitas Galuh, 2026)
Women Farmers Groups (KWT) play an important role in increasing women’s participation in the agricultural sector through the strengthening of communication networks. This study aims to analyze the relationship between individual characteristics and members positions in the communication network of the KWT KSB in Sukaraja Village, Bogor Regency. The individual characteristics examined include age, education level, occupation, and number of children. The study employed a quantitative approach with a survey method conducted among KWT KSB members. Data were analyzed using Social Network Analysis (SNA) through centrality measures (degree, closeness, betweenness, and eigenvector), as well as Spearman’s non-parametric statistical test to examine the relationship between variablesThe results indicate that education level and number of children significantly correlate with members positions in the network, particularly in betweenness and eigenvector centrality, while age and employment status show no significant effect. Members with higher education and a moderate number of children tend to act as connectors and exert greater influence in information flow. This study highlights the importance of empowering members with lower education and limited resources to enhance their participation in the communication network, thereby improving overall engagement and sustainability of KWT activities. The findings contribute to strengthening social dynamics within the group and developing community-based women empowerment strategies.